Does Access to Citizenship Confer Socio-Economic Returns? Evidence from a Randomized Control Design - Jens Hainmueller; Elisa Cascardi; Michael Hotard; Rey Koslowski; Duncan Lawrence; Vasil Yasenov; David D. Laitin (Institute of Labor Economics (IZA), 2023)
Based on observational studies, conventional wisdom suggests that citizenship carries economic benefits. We leverage a randomized experiment from New York where low-income registrants who wanted to become citizens entered a lottery to receive fee vouchers to naturalize. Voucher recipients were about 36 p.p. more likely to naturalize. Yet, we find no discernible effects of access to citizenship on several economic outcomes, including income, credit scores, access to credit, financial distress, and employment. Leveraging a multi-dimensional immigrant integration index, we similarly find no measurable effects on non-economic integration. However, we do find that citizenship reduces fears of deportation. Explaining our divergence from past studies, our results also reveal evidence of positive selection into citizenship, suggesting that observational studies of citizenship are susceptible to selection bias.
Keywords: G51; J15; J31; 330; citizenship; naturalization; immigrant integration